(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the development, analytical dependencies have been derived for determining the stability of the technological system during turning of rotary parts. Cases such as establishment in a chuck, in dead center and between centers have been analysed. The results of the analytical studies will contribute post-processing accuracy to be determined and predicted.